Late discover of a traumatic cardiac injury: Case report - C, Benlafqih; H, Bouhdadi; A, Bakkali; J, Rhissassi; R, Sayah; M, Laaroussi (Journal of Cardiology and Cardiovascular Medicine, 2019)
Blunt chest trauma leads to a wide range of lesions, relatively minor parietal injuries to potentially fatal cardiac lesions, making diagnosis and management difficult. The diagnosis is currently facilitated by imaging, however, these lesions may go unnoticed and be discovered late through complications. We report the case of a neglected heart wound revealed by a heart failure. This case is notable due to a favourable outcome despite a delay in diagnosis due to a lack of pericardial effusion and the absence of cardiac symptoms, and a long delay from injury to appropriate treatment in the presence of a penetrating cardiac wound deep enough to cause a muscular ventricular septal defect and lacerate the anterior mitral leaflet.